Math Error Types and Correlates in Adolescents with and without Attention Deficit Hyperactivity Disorder - Capodieci, Agnese; Martinussen, Rhonda (Frontiers in Psychology, 2017)
Objective: The aim of this study was to examine the types of errors made by youth with and without a parent-reported diagnosis of attention deficit and hyperactivity disorder (ADHD) on a math fluency task and investigate the association between error types and youths’ performance on measures of processing speed and working memory. Method: Participants included 30 adolescents with ADHD and 39 typically developing peers between 14 and 17 years old matched in age and IQ. All youth completed standardized measures of math calculation and fluency as well as two tests of working memory and processing speed. Math fluency error patterns were examined. Results: Adolescents with ADHD showed less proficient math fluency despite having similar math calculation scores as their peers. Group differences were also observed in error types with youth with ADHD making more switch errors than their peers. Conclusions: This research has important clinical applications for the assessment and intervention on math ability in students with ADHD.